2012
DOI: 10.1186/1471-2458-12-993
|View full text |Cite
|
Sign up to set email alerts
|

Subjective health complaints in older adolescents are related to perceived stress, anxiety and gender – a cross-sectional school study in Northern Sweden

Abstract: BackgroundNegative trends in adolescent mental and subjective health are a challenge to public health work in Sweden and worldwide. Self-reported mental and subjective health complaints such as pain, sleeping problems, anxiety, and various stress-related problems seem to have increased over time among older adolescents, especially girls. The aim of this study has therefore been to investigate perceived stress, mental and subjective health complaints among older adolescents in Northern Sweden.MethodsData were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
190
2
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(250 citation statements)
references
References 70 publications
33
190
2
18
Order By: Relevance
“…Strong associations have also been found for perceived stress, psychosomatic symptoms, and anxiety (Wiklund et al, 2012). There is also growing evidence of a significant relationship between psychosocial stress and psychopathology in children and adolescents from both cross-sectional (Compas, 1987;Compas, Connor-Smith, Saltzman, Thomsen, & Wadsworth, 2001) and longitudinal studies (Hammen & Goodman-Brown, 1990;Hilsman & Garber, 1995;Rudolph, Lambert, Clark, & Kurlakowsky, 2001;Schmeelk-Cone & Zimmerman, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Strong associations have also been found for perceived stress, psychosomatic symptoms, and anxiety (Wiklund et al, 2012). There is also growing evidence of a significant relationship between psychosocial stress and psychopathology in children and adolescents from both cross-sectional (Compas, 1987;Compas, Connor-Smith, Saltzman, Thomsen, & Wadsworth, 2001) and longitudinal studies (Hammen & Goodman-Brown, 1990;Hilsman & Garber, 1995;Rudolph, Lambert, Clark, & Kurlakowsky, 2001;Schmeelk-Cone & Zimmerman, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…One study used three scales (the internationally validated Hospital Anxiety and Depression (HAD) scale, a questionnaire measuring perceived stress and sleep and a questionnaire measuring subjective health complaints) on upper secondary school students aged 16-17 years from northern Sweden in [2007][2008]. The study showed a high prevalence of subjective health complaints and perceived stress, particularly among adolescent girls (Wiklund et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is related to poorer SRH, and a recent study from the SALLS study population showed increasing BMI in all cohorts over the same study period, especially in younger cohorts, with larger annual increases in BMI in females aged 24-39 years and in males aged 32-47 years (Caman et al 2013;Marques-Vidal et al 2012). Earlier studies have reported increases in mental health complaints, anxiety, and stress among adolescents, especially girls (Hagquist 2010;Wiklund et al 2012). …”
Section: Discussionmentioning
confidence: 90%